The numinosity of soul: Andre Delbecq's legacy for MSR. Issue 1 (1st January 2020) - Fry, Louis W.
ABSTRACT: The purpose of this piece is to offer a sense of Andre Delbecq as the pioneering founder of management, spirituality, and religion (MSR) as a field of scholarly inquiry. In his unique way, André, informed by his solid knowledge of organizational processes and his Christian faith, integrated spirituality into his teaching and scholarship. First I offer an overview of his early career roots which laid the foundation for this work and the impetus for his work on MSR, which defined the later years of his long and distinguished career. Then I review the context and motivations that led to his offering a seminar on Spirituality for Organizational Leadership, from which evolved what he saw as successful strategies for MSR scholarship and teaching. Next, comes an overview of his view of the fundamental role MSR should play in organizational design and culture, with an emphasis on teamwork and decision-making. Following this is an exploration of his groundbreaking work on leadership formation with a focus on the spiritual journey, discernment, and humility as an offset to hubris. Finally his thoughts concerning "Where do we go from here' are offered.